Genetically Modified Food - Keith R. Schneider; Renée M. Goodrich-Schneider (EDIS)
Revised! FSHN02-2, a 3-page fact sheet by Keith R. Schneider and Renee Goodrich Schneider, defines and describes the different kinds of genetically modified foods, explains possible advantages and possible concerns, and gives examples of GM foods in use today. Updated to reflect more current information. Published by the UF Department of Food Science and Human Nutrition, November 2006.